CHANGES IN PARAMETERIZATIONS OF REGIONAL CLIMATE MODEL REGCM4.4.5: THE ROLE OF LAND COVER ON REGIONAL CLIMATE OVER MEDITERRANEAN - Velikou, K.; Tolika, K.; Anagnostopoulou, Ch. (Bulletin of the Geological Society of Greece, 2016)
A parameter that affects significantly the local, regional and global climate system is land cover and the changes that may occur to it. During winter season, heavy precipitation assists vegetation growth of Mediterranean forests and woodlands, whereas during summer, absence of precipitation and severe heat waves result to arid and semiarid vegetation. For that reason, it was quite interesting to track the changes that may occur in the climate of the Mediterranean region due to land cover/land use changes on regional climate over the Mediterranean region. The main objective of the study is the assessment of the impacts of land cover/land use changes on regional climate over the Mediterranean region. The examined regional climate model used in the study is RegCM4.4.5. Its spatial resolution is 25x25km and different simulations were performed with changes in land cover/land use for the time period 1981-1990. The different simulated data were compared in order to examine the modifications that occur from land cover/land use changes in evapotranspiration and surface albedo to direct and diffuse radiation in the domain of study.